1991
DOI: 10.1042/bj2760053
|View full text |Cite
|
Sign up to set email alerts
|

Topography of very-long-chain-fatty-acid-activating activity in peroxisomes from rat liver

Abstract: We have investigated the localization of palmitoyl-CoA (hexadecanoyl-CoA) synthetase (EC 6.2.1.3) and cerotoyl-CoA (hexacosanoyl-CoA) synthetase in peroxisomes isolated from rat liver. Palmitoyl-CoA and cerotoyl-CoA synthetases, like acyl-CoA: dihydroxyacetone phosphate acyltransferase (EC 2.3.1.42), are present in the peroxisomal membrane. Trypsin treatment of intact peroxisomes led to the disappearance of both palmitoyl-CoA and cerotoyl-CoA synthetase activities but had little, if any, effect on L-alpha-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Similarly, ALDP could import VLCFA-CoA into peroxisomes following dimerization with itself or a partner. Whether the active site of the mammalian VLACS is located on the cytoplasmic or luminal side of peroxisomes remains unclear (33,34). If it is located within peroxisomes, this would rather support that ALDP transports VLCFA or a substrate necessary to VLACS activation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ALDP could import VLCFA-CoA into peroxisomes following dimerization with itself or a partner. Whether the active site of the mammalian VLACS is located on the cytoplasmic or luminal side of peroxisomes remains unclear (33,34). If it is located within peroxisomes, this would rather support that ALDP transports VLCFA or a substrate necessary to VLACS activation.…”
Section: Discussionmentioning
confidence: 99%
“…An identical enzyme is present on the outer mitochondrial mem brane and the membrane of the ER (83) . Whereas Lazo et al (87) reported that the active site faces the peroxisomal interior, Lageweg et al (88) found a cytosolic orientation. A similar activity was detected in the ER but not in mitochondria (85 , 86).…”
Section: Enzymic Organizationmentioning
confidence: 99%
“…3). Whether VLCFA are activated intraperoxisomally or outside the peroxisome (and then transported into the organelle as VLCFA-CoA) has been the subject of some debate [1519]. …”
Section: Peroxisomal Pathways Requiring Activated Fasmentioning
confidence: 99%
“…lignoceric acid; C24:0), and branched-chain FAs phytanic acid and pristanic acid [19]. The topographic orientation of ACSVL1 in the peroxisomal membrane has not completely been resolved [1519]. Investigations into the function of the peroxisomal membrane protein ABCD1, which is defective in X-linked adrenoleukodystrophy, suggests that VLCFA are activated extraperoxisomally via ACSVL1 (or another ACS) oriented facing the cytoplasm, after which the CoA derivatives are transported into the organelle by ABCD1 [81].…”
Section: Peroxisomal Acssmentioning
confidence: 99%